Preeclampsia induced by cadmium in rats is related to abnormal local glucocorticoid synthesis in placenta - Wang, Fan (Reprod Biol Endocrinol, 2014)
BACKGROUND: Cadmium (Cd) is a major environmental pollutant that causes multiple adverse health effects in humans and animals. In this study, we investigated Cd-mediated toxic effects in rats during pregnancy and endocrine intervention in the placenta. METHODS: We exposed pregnant rats to intraperitoneal Cd (CdCl2) at various doses (0, 0.25, and 0.5 mg/kg BW/day) from days 5 to 19 of pregnancy and evaluated the maternal-placental-fetal parameters linked to preeclampsia. We measured the corticosterone level in rat serum and placental tissue by sensitive ELISA and also analyzed the expression of glucocorticoid synthesis enzymes in the placenta. RESULTS: Key features of preeclampsia (PE), including hypertension, proteinuria, glomerular endotheliosis, placental abnormalities and small fetal size, appeared in pregnant rats after injection with 0.5 mg/kg BW/day Cd. The placental corticosterone production and maternal and fetal plasma corticosterone levels were increased in rats treated with 0.5 mg/kg BW/day Cd (P <0.01). The expression of 21-hydroxylase (CYP21) and 11beta-hydroxylase (CYP11B1), enzymes essential for corticosteroid synthesis, were increased in Cd-exposed placenta (P <0.01). 11beta-hydroxysteroid dehydrogenase (11beta-HSD2), a dominant negative regulator of local glucocorticoid levels, was decreased in Cd-exposed placenta (P <0.01). CONCLUSIONS: Our study demonstrates for the first time that changes in placental glucocorticoid synthesis induced by Cd exposure during pregnancy could contribute to preeclamptic conditions in rats.